Scaling effects of temperature on parasitism from individuals to populations. Issue 10 (9th August 2022) - Kirk, Devin; O'Connor, Mary I.; Mordecai, Erin A.
Abstract: Parasitism is expected to change in a warmer future, but whether warming leads to substantial increases in parasitism remains unclear. Understanding how warming effects on parasitism in individual hosts (e.g. parasite load) translate to effects on population‐level parasitism (e.g. prevalence, R0 ) remains a major knowledge gap. We conducted a literature review and identified 24 host–parasite systems that had information on the temperature dependence of parasitism at both individual host and host population levels: 13 vector‐borne systems and 11 environmentally transmitted systems. We found a strong positive correlation between the thermal optima of individual‐ and population‐level parasitism, although several of the environmentally transmitted systems exhibited thermal optima >5°C apart between individual and population levels. Parasitism thermal optima were close to vector performance thermal optima in vector‐borne systems but not hosts in environmentally transmitted systems, suggesting these thermal mismatches may be more common in certain types of host–parasite systems. We also adapted and simulated simple models for both types of transmission modes and found the same pattern across the two modes: thermal optima were more strongly correlated across scales when there were more traits linking individual‐ to population‐level processes. Generally, our results suggest that information on the temperature dependence, and specifically the thermal optimum, at either the individual or population level should provide a useful—although not quantitatively exact—baseline for predicting temperature dependence at the other level, especially in vector‐borne parasite systems. Environmentally transmitted parasitism may operate by a different set of rules, in which temperature dependence is decoupled in some systems, requiring the need for trait‐based studies of temperature dependence at individual and population levels. Abstract : Understanding effects of temperature on both individuals and populations is critical for disease mitigation efforts as the world warms. These results suggest that information on temperature dependence at either the individual or population level should provide a useful, although not quantitatively exact, baseline for predicting temperature dependence at the other level.